Adrenal bleeding due to pheochromocytoma - A call for algorithm - Rzepka, Ewelina; Kokoszka, Joanna; Grochowska, Anna; Ulatowska-Białas, Magdalena; Lech, Martyna; Opalińska, Marta; Przybylik-Mazurek, Elwira; Gilis-Januszewska, Aleksandra; Hubalewska-Dydejczyk, Alicja (Frontiers in Endocrinology, 2022)
Background Adrenal hemorrhage is a rare, usually life-threating complication. The most common neoplasm resulting in spontaneous adrenal bleeding is pheochromocytoma and it accounts for nearly 50% of cases. Currently, the recommendations for the diagnosis and management of patients with adrenal bleeding due to pheochromocytoma are unavailable. Materials and Methods: We performed a database search for all pheochromocytoma patients, diagnosed and treated from 2005 to 2021 in tertiary endocrinology centre. 206 patients were identified, 183 with complete data were included in the analysis. We investigated clinicopathological characteristics, treatment and outcomes of hemorrhagic pheochromocytoma cases and characterize our approach to perioperative diagnosis and medical management. Finally our experiences and data from previously published articles concerning adrenal hemorrhage were analysed to propose a diagnostic and therapeutic algorithm for hemorrhagic pheochromocytomas. Results: In the whole group, seven patients (4 men and 3 women) with adrenal bleeding were found, (3.8%). Median patient’s age was 49 years (range: 36-78 years). The most common manifestation of adrenal bleeding was acute abdominal pain (5/7). Two patients developed shock. Hormonal assessment was performed in five patients, based on 24-hour urinary fractionated metanephrines with urinary 3-methoxytyramine. Normetanephrine was elevated in all patients, metanephrine and 3-methoxytyramine - in four cases (4/5). Most patients (6/7) had symptoms suggesting pheochromocytoma before hemorrhage – most commonly paroxysmal hypertension (4/7). One patient died, before the diagnosis of adrenal bleeding was made. Diagnostic imaging performed in six out of seven patients revealed adrenal tumour, with median largest diameter equal to 7.4 cm (range: 5-11 cm). Five patients had elective surgery, in one case an urgent surgery was performed. In all cases the diagnosis of pheochromocytoma was confirmed in postoperative histopathology or in autopsy. The perioperative survival rate was 85.7%. Conclusions: Diagnosis of pheochromocytoma should be always considered in patients with adrenal bleeding, especially with accompanying abdominal pain, hemodynamic shock and previous history of pheochromocytoma-associated symptoms. Lack of proper diagnosis of pheochromocytoma before surgery is associated with an additional perioperative risk. To improve the decision making in this life-threatening clinical situation, based on our results and literature data, we proposed a diagnostic and treatment algorithm.